Do religious beliefs explain preferences for income redistribution? Experimental evidence - Ilja Neustadt (University of Zurich, Socioeconomic Institute, 2010)
Due to the mixed empirical evidence bearing on the economic determinants, beliefs have been at the center of attention of research into preferences for income redistribution. We elicit preferences for income redistribution through a Discrete Choice Experiment performed in 2008 in Switzerland and relate them to several behavioral determinants, in particular to religious beliefs. Estimated marginal willingness to pay (WTP) is positive among those who do not belong to a religious denomination, and negative otherwise. However, the marginal WTP is shown to increase with a higher degree of religiosity. Moreover, those who state that luck or connections play a crucial role in determining economic success exhibit significantly higher WTP values than those who deem effort to be decisive.
Keywords: C35; C93; D63; H29; 330; income redistribution; beliefs; religiosity; welfare state; preferences; willingness to pay; discrete choice experiments; Einkommensverteilung; Öffentliche Meinung; Religion; Willingness to pay; Diskrete Entscheidung; Test; Schweiz